Association patterns between farmland abandonment and the non-native Common Waxbill (Estrilda astrild) in the eastern Iberian Peninsula - Pau Lucio-Puig; Rafael Muñoz-Mas; Virginia Garófano-Gómez; Hugo Merle; Jaime Gómez; Juan S. Monrós (Journal of Ornithology, 2025)
Pet trading has led to a growing number of bird introductions worldwide, which has negatively affected recipient ecosystems and native species. Studying the seasonal and spatial distribution patterns of native and non-native bird species, such as the Common Waxbill ( Estrilda astrild ), is fundamental for understanding the ecological interactions between these two groups of species. For this purpose, we ran a year-round survey of passerine communities in two Mediterranean wetlands of the eastern Iberian Peninsula and investigated Common Waxbill’s feeding preferences. We studied the Common Waxbill association with native birds and their habitat use. The cluster analysis indicated that the Common Waxbill was the most abundant species of a distinct community, with peak presence in autumn. The random forests analysis revealed that it preferred human-modified land uses. Furthermore, farmland abandonment and the presence of two invasive plants, Pampas Grass ( Cortaderia selloana ) and Giant Reed ( Arundo donax ), positively influenced Common Waxbill presence. However, when eaten plants were divided into native, non-native and invasive, the Common Waxbill did not exhibit any preference. This corroborates that the Common Waxbill has significant ecological plasticity, which allows it to exploit a wide range of feeding resources in human-modified habitats. This study enhances knowledge of the interactions between native birds and invasive plants due to farmland abandonment, and of one of the most globally widespread non-native bird species. It highlights the need to monitor both groups of species and their long-term interactions.

An appraisal of the ages of Phanerozoic large igneous provinces - Qiang Jiang; Fred Jourdan; Hugo K.H. Olierook; Renaud E. Merle (Earth-Science Reviews, 2023)

Mating system of Centaurea aspera ( asteraceae ) polyploid relatives - Short communication - María Ferriol; Alfonso Garmendia; David Benavent; P. Pablo Ferrer-Gallego; Hugo Merle (Plant Biosystems, 2021)

Ecological germination requirements of the aggregate species Teucrium pumilum (Labiatae) endemic to Spain - María Ferriol; Isabel Pérez; Hugo Merle; Herminio Boira (Plant and Soil, 2006)